Modified Genetic Algorithm to Model Crystal Structures: III. Determination of Crystal Structures Allowing Simultaneous Molecular Geometry Relaxation - Bazterra, Victor E. (2004)
The modified genetic algorithm (MGAC) has been extended to allow simultaneous relaxation of molecular geometry during optimization of the crystalline structure. The method was applied to L-alanine and DL-alanine for two different potential functions. The genetic algorithm was always able to find minima that are likely global minima of the crystalline potential, showing good agreement with the experimental structures. For DL-alanine MGAC located the experimental crystalline structure but also consistently found a different low-energy crystalline structure that it is an excellent candidate for a polymorph. © 2003 Wiley Periodicals, Inc.